2021
DOI: 10.3390/aerospace8080232
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft Engine Gas-Path Monitoring and Diagnostics Framework Based on a Hybrid Fault Recognition Approach

Abstract: Considering the importance of continually improving the algorithms in aircraft engine diagnostic systems, the present paper proposes and benchmarks a gas-path monitoring and diagnostics framework through the Propulsion Diagnostic Methodology Evaluation Strategy (ProDiMES) software developed by NASA. The algorithm uses fleet-average and individual engine baseline models to compute feature vectors that form a fault classification with healthy and faulty engine classes. Using this classification, a hybrid fault-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Table 7 summarises the blind-test-case metric results from other known diagnostic methods using the ProDiMES software for evaluation. Regularized Extreme Learning Machines-Sparse Representation Classification (RELM-SRC) method [33] has the best diagnostic performance, which provides a kappa coefficient of 0.685. The kappa coefficient of the proposed method in this paper is 0.731, which is 0.046, larger than the kappa coefficient provided by the RELM-SRC method.…”
Section: Discussionmentioning
confidence: 99%
“…Table 7 summarises the blind-test-case metric results from other known diagnostic methods using the ProDiMES software for evaluation. Regularized Extreme Learning Machines-Sparse Representation Classification (RELM-SRC) method [33] has the best diagnostic performance, which provides a kappa coefficient of 0.685. The kappa coefficient of the proposed method in this paper is 0.731, which is 0.046, larger than the kappa coefficient provided by the RELM-SRC method.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al confirmed better performance provided by Soft Extreme Learning Machine (SELM) and Improved SELM (ISELM) [24]. To improve numerical stability, a regularization term is often used in ELM diagnostic systems [25][26][27]. Liu et al introduced the optimized ELM based on restricted Boltzmann machine [28] to predict the EGT trend in Auxiliary Power Unit (APU) with the improved stability of ELM solutions when some input parameters are correlated.…”
Section: Introductionmentioning
confidence: 97%
“…Here, the data sparsity related to snapshot data leads to difficulties distinguishing between faults and random scatter. Depending on the faulty component and the severity of the fault, it may take multiple data points to detect a fault [4][5][6]. Consequently, several flights might be carried out until fault detection increasing the risk of collateral damage.…”
Section: Introductionmentioning
confidence: 99%